The evaluation of properties of coal water slurries under hydrodynamic conditions - Bilecky, V. S.; Krut’, O.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The behavior of high-concentration coal water slurry (CWS) under dynamic conditions has been considered on the basis of fundamental assumptions of the theory of aggregated stability of lyophobic dispersed systems. The obtained results have been compared with the applied technical characteristics of hydraulic transport of CWS.